A 20 Gbps Integrated Polarization Division Multiplexed-Free Space Optics Transmission System: Impact of Saudi Arabia’s Jazan Region Weather Conditions - Ali Hakami; Din, Jafri; Omar Abdul Aziz; Khalid Alkhedhairi; Abdulrahman Ghazwani; Mofarh Al-hrooby (ELEKTRIKA- Journal of Electrical Engineering, 2025)
This paper explores the performance analysis of a polarization division multiplexing (PDM) free space optical (FSO) transmission system based on specific weather conditions of Jazan region, in Saudi Arabia. The non-return-to-zero (NRZ) modulated 1550 nm optical signal is employed to transmit two independent data streams at a rate of up to 10 Gbps each over two orthogonal polarization states. Visibility data for Jazan region were retrieved from the Saudi Arabia Meteorological Department during a period of one year that extends between January 1 and December 31, 2023, to model atmospheric impact on signal transmission. All three models, Kim model, Kruse Model and Al-Naboulsi Model were considered to calculate atmospheric attenuation coefficients with the values being 0.59 dB/km, 0.60 dB/km and2.07dB/km respectively. By increasing the transmission range, performance metrics such as Q Factor and bit error rate (BER) curves were investigated to verify robustness of the system against different levels of attenuation. The results suggest that this system will have a Q Factor and BER within the accepted values for over 8000 m of coverage if Kim & Kruse models are considered. Nevertheless, the maximum possible range drops to 4500 m with the Al-Naboulsi model because it estimates higher attenuation. The study shows the efficiency and limitation of PDM-based FSO system under different attenuation models which reveal variation of adequacy range performances based on Jazan region’s atmospheric conditions. The results of this research will assist in developing a more practical design for FSO systems under similar atmospheric conditions to guarantee high-speed and reliable optical communication.